2010
DOI: 10.4081/ija.2010.323
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Management Zones Using Soil Properties and a Multivariate Geostatistical Approach

Abstract: Agricultural fields naturally have within-field variations that may cause spatial variability in crop yields. Delineating a field into a few management zones (MZ) is therefore a practical management approach for precision agriculture. In this study, some soil properties (clay content, organic matter content and water content measured at different dates) and a multivariate geostatistical approach were used to delineate management zones. The temporal stability of soil water content spatial patterns may be an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Recent studies pointed out that site specific harvesting bears potential to increase wheat quality and net return rates in quality incentive markets (Morari et al 2013;Diacono et al 2012;Meyer-Aurich et al 2008;Wright et al 2004;Freeman et al 2003). In accordance with previous studies, Diacono et al (2012) reported that climatic conditions, especially available soil water, play a major role in affecting the spatial patterns of yield as well as other quality parameters of wheat crops in rain fed agricultural systems (Buttafuoco et al 2010;Ibrahim & Huggins 2011;Basso et al 2007). Practically, the longer the duration and slower the rate of senescence, the greater is the probability for higher yields (Herbek & Lee 2009).…”
Section: Introductionsupporting
confidence: 70%
“…Recent studies pointed out that site specific harvesting bears potential to increase wheat quality and net return rates in quality incentive markets (Morari et al 2013;Diacono et al 2012;Meyer-Aurich et al 2008;Wright et al 2004;Freeman et al 2003). In accordance with previous studies, Diacono et al (2012) reported that climatic conditions, especially available soil water, play a major role in affecting the spatial patterns of yield as well as other quality parameters of wheat crops in rain fed agricultural systems (Buttafuoco et al 2010;Ibrahim & Huggins 2011;Basso et al 2007). Practically, the longer the duration and slower the rate of senescence, the greater is the probability for higher yields (Herbek & Lee 2009).…”
Section: Introductionsupporting
confidence: 70%
“…The delineation of site-specific management zones can play an important role in addressing the spatial variability effects by defining homogenous sub-field areas within an entire field. Defining the sub-field areas is difficult due to complex interactions between many factors such as climate, topography and soil properties (Buttafuoco et al 2010;Moral et al 2011). In some cases, interaction between these factors induces spatial variability and affects crop yield (Bakhsh et al 2000;Mzuku et al 2005;Bakhsh & Kanwar 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Defining the sub-field areas is difficult due to complex interactions between many factors such as climate, topography and soil properties (Buttafuoco et al . 2010; Moral et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the number of spatial processes and their respective scales is a critical point in geostatistical models. In the applications of LMC to multivariate spatial analysis (see, e.g., Webster et al, ; Castrignanó et al, ; Buttafuoco et al, ), the spatial correlation functions , the parameters , and r are obtained from empirical estimates of the auto‐ and cross‐variograms before any modeling. This approach ignores the uncertainty in the estimates of the spatial parameters and may yield dubious inference.…”
Section: Model Constructionmentioning
confidence: 99%